Integration of Financial Literacy and Psychology: An Analysis of the Influence of Locus of Control on the Effectiveness of Generation Z Financial Management in Tangerang City - Fitriana, Amalia Indah; Mikrad, Mikrad; Yoga, Randi Febri (Digital Business Journal, 2025)
Generation Z in Tangerang City faces challenges in managing personal finances, influenced by low financial literacy, limited access to formal finance, and lack of self-control over financial decisions. This study analyzes the influence of financial literacy, financial inclusion, and locus of control on the financial management of Generation Z, filling the research gap in the Indonesian urban context. The explanatory quantitative method was used with survey data from 220 Generation Z respondents in Tangerang who were purposively selected. The results showed that the three variables had a positive and significant effect, with financial literacy as the most dominant factor, followed by locus of control and financial inclusion. These findings reinforce the importance of improving financial literacy and access to inclusive finance to drive better financial management. The novelty of the research lies in an integrative approach between cognitive aspects (literacy), access (inclusion), and psychological (locus of control) in the context of urban generation Z. Practically, this study recommends strengthening digital-based financial education programs and collaboration between stakeholders to increase financial literacy and inclusion of the younger generation. Theoretical contributions include the development of financial behavioural models that blend external and internal factors, while policy contributions emphasise the need for structured interventions to support the financial stability of Generation Z